30-Day Readmission Rate as an Indicator of the Quality of Elective Surgical Inpatient Care at one of the Eastern Province’s Hospitals, Kingdom of Saudi Arabia - Azza A. El Mahalli; Heba Y. Al-Nujaidi; Nourah A. Al-Turaiyef; Sara S. Al-Rashed; Salha F. Al-Asiri (Journal of King Abdulaziz University: Medical Sciences, 2023)
30-day re-admission rate is a performance indicator used to reflect adverse events and complications of treatment. High rates could indicate poor quality of care and clinical incompetence. The study aims to measure a 30-day readmission rate as a performance indicator of the quality of elective surgical inpatient care at teaching hospitals, and to determine predictors and reasons of readmission. This is a retrospective cohort study and conducted in some surgical departments. Target populations were patients that underwent any of the elective operations, and readmitted for unplanned related reasons within 30-days for four consecutive years (2006-2009). However, patients not readmitted were those that underwent any of the elective operations and not readmitted within 30-days. Data were extracted from the computerized and paper medical records. Multivariate regression analysis determines predictors of readmission (rate of 20.4%) on preoperative and postoperative length of stay >3 days. Hence, major operation and lack of discharge plan for follow up. However, co morbidities other than diabetes mellitus and hypertension were protective. Majority of reasons of readmission were infection, then bleeding. The hospital should manage pre and post operative stay properly, emphasize the role of discharge plan and apply infection control surveillance.